1976
DOI: 10.1104/pp.57.6.928
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Nitrate Reductase Activity in Leaves of Capsicum annuum L. and the Influence of Kinetin

Abstract: In the expanding leaves of Capsicum annuum L. cv. California Wonder, two of the three peaks of nitrate reductase activity associated with the light period exhibit a circadian rhythm that persists in continuous light.The spray application of kinetin to the whole shoot or to leaves other than the ones used for nitrate reductase assay causes a phase shift in the activity peaks and this has been used in preliminary investigations of the character of the mechanisms controlling the timing of the peaks.There was some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 24 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Observations on diurnal centrations when stipplied with noti-Smiting nitrate con-variation in NR activity are numerous for both in vitro centrations in the growth medium (Steingrover et al (e.g. Lillo 1983, Nicholas et al, 1976, Steer 1976) and in 1982). Light, temperature and nitrate supply to the vivo activity (Lillo and Henriksen 1984, Rajagopal et al roots can exert their influence via changes in nitrate up-1977, Stuith and.…”
Section: Introductionmentioning
confidence: 99%
“…Observations on diurnal centrations when stipplied with noti-Smiting nitrate con-variation in NR activity are numerous for both in vitro centrations in the growth medium (Steingrover et al (e.g. Lillo 1983, Nicholas et al, 1976, Steer 1976) and in 1982). Light, temperature and nitrate supply to the vivo activity (Lillo and Henriksen 1984, Rajagopal et al roots can exert their influence via changes in nitrate up-1977, Stuith and.…”
Section: Introductionmentioning
confidence: 99%
“…Diurnal rhythms in NRA3 in leaves (1,15), as well as apparently endogenous rhythms in activity (16) are well known. A recent publication (14) has established that the removal of shoots from cotton roots led to a marked decline in NRA assayed (in vivo) and in sugar content in the roots, but it is not clear if any indirect light-mediated control of NRA is sustained at different times during the photoperiod.…”
mentioning
confidence: 99%
“…Statistically significant results were obtained that suggested that protein(s) with molecular weights of 26,000 daltons were preferentially synthesized in the photoperiod compared to the dark period. No evidence was found for the differential synthesis of proteins within the photoperiod.The reduction of nitrate exhibits a marked periodicity with three peaks of activity during the photoperiod, in leaves of Capsicum annuum (18,19). The consequent variability in the supply of reduced nitrogen is reflected in the amino acid pool size in the leaves (13,16) and there is an indication of an integrated control of carbon supply and reduced nitrogen supply for amino acid synthesis (17).…”
mentioning
confidence: 99%
“…The reduction of nitrate exhibits a marked periodicity with three peaks of activity during the photoperiod, in leaves of Capsicum annuum (18,19). The consequent variability in the supply of reduced nitrogen is reflected in the amino acid pool size in the leaves (13,16) and there is an indication of an integrated control of carbon supply and reduced nitrogen supply for amino acid synthesis (17).…”
mentioning
confidence: 99%